High-performance capacitive pressure sensors Fabricated by introducing dielectric filler and conductive filler into a porous dielectric layer through a Biomimic strategy. (18th August 2022) - Ma, Zhuyu; Zhang, Kaiyi; Yang, Shengdu; Zhang, Yang; Chen, Xianchun; Fu, Qiang; Deng, Hua
Abstract: Capacitive sensors have vast application prospects. Their dielectric layer is hardened under high pressure, the sensitivity is reduced and sensing behavior is nonlinear. To tackle this, a novel strategy is used to incorporate voids, dielectric filler and conductive filler into the dielectric layer. Firstly, "root" like dendritic colloid polyurethane (DCPU) is prepared to grasp different content of carbon nanotube (CNT) and barium titanate (BaTiO3, BT), before such hybrid filler is coated onto the backbone of PU foam. For capacitive pressure sensors, it is observed that sensitivity increases with increasing filler content. More importantly, the addition of CNT into the inner layer of hybrid filler containing BT in the outer layer leads to linear pressure sensing behavior in a wide pressure range. Furthermore, the overall performance achieves a sensitivity of 2.51 kPa −1 under 0–100 kPa and a linearity of R 2  = 0.9989, and stable signals after 1000 cycles. Finally, it is successfully demonstrated that petals with a weight of 96 mg and the physiological signals of the human body such as heartbeat, swing arm amplitude, and joint bending can be detected. This work provides a new design inspiration for capacitive sensors with high sensitivity and high linearity in realizing medical health monitoring and motion detection. Graphical abstract: Introducing conductive/dielectric fillers into porous dielectric layers to study their capacitance-sensitive behavior. Image 1